The perception of affective touch in Parkinson's disease and its relation to small fibre neuropathy. (28th November 2016) - Kass‐Iliyya, Lewis; Leung, Matthew; Marshall, Andrew; Trotter, Paula; Kobylecki, Christopher; Walker, Susannah; Gosal, David; Jeziorska, Maria; Malik, Rayaz A.; McGlone, Francis; Silverdale, Monty A.
Abstract: Affective touch sensation is conducted by a sub‐class of C‐fibres in hairy skin known as C‐Tactile (CT) afferents. CT afferents respond maximally to gentle skin stroking at velocities between 1 and 10 cm/s. Parkinson's disease (PD) is characterised by markedly reduced cutaneous C‐fibres. It is not known if affective touch perception is influenced by C‐fibre density and if affective touch is impaired in PD compared to healthy controls. We predicted that perceived pleasantness to gentle stroking in PD would correlate with C‐afferent density and that affective touch perception would be impaired in PD compared to healthy controls. Twenty‐four PD patients and 27 control subjects rated the pleasantness of brush stroking at an optimum CT stimulation velocity (3 cm/s) and two sub‐optimal velocities (0.3 and 30 cm/s). PD patients underwent quantification of C‐fibre density using skin biopsies and corneal confocal microscopy. All participants rated a stroking velocity of 3 cm/s as the most pleasant with significantly lower ratings for 0.3 and 30 cm/s. There was a significant positive correlation between C‐fibre density and pleasantness ratings at 3 and 30 cm/s but not 0.3 cm/s. Mean pleasantness ratings were consistently higher in PD patients compared to control subjects across all three velocities. This study shows that perceived pleasantness to gentle touch correlates significantly with C‐fibre density in PD. The higher perceived pleasantness in PD patients compared to controls suggests central sensitisation to peripheral inputs, which may have been enhanced by dopamine therapy. Abstract : We investigated pleasantness induced by cutaneous tactile stimulation in Parkinson's disease patients using different stroking velocities. We also used 2 separate measures of small fibre nerve density – skin biopsy and corneal confocal microscopy. This figure demonstrates a relationship between perceived pleasantness ratings and both measures of small fibre neuropathy.